Environmental Impact Mitigation of Solid Particles in Municipal Wastewater Arriving to Sea using Submarine Outfalls Systems. Case Study: Proposed Submarine Outfall for the Southern Part of Latakia - شيبان ساميه (Latakia University Journal -Engineering Sciences Series, 2022)
Many coastal cities around the world employ submarine outfall systems to safely discharge municipal wastewater into the marine environment. These outfalls vary in length and upstream treatment of the discharged wastewater. Considering that almost all outfalls in Latakia discharge wastewater directly onshore, they cause the accumulation of pollutants at beach which negatively affects the aesthetic, health and environmental aspects. This research proposes a submarine outfall system for the urban community at south Latakia, then it moves to study the fate of suspended solid particles, driven with wastewater into the receiving water, because of the pollutants they carry and the turbidity they cause and as a long-term pollution compared to bacterial pollution. The study is performed by coupling suspended solids deposition model with Lagrangian model that describes hydrodynamic behavior of buoyant jets. The case study was one of buoyant jets of the diffuser in the proposed submarine outfall in operating conditions close to real conditions. The study found that in normal conditions (still water and in presence of moderate current) the majority of solid particles of settling velocity 3-5 cm/s depose in the nearfield and their quantity must be minimized upstream, while solid particles with settling velocity inferior to 0.3 cm/s have the tendency to depose out of nearfield or stay suspended in water. These findings support that, wastewater before discharging, might undergo an enhanced primary treatment that can be designed economically and sustainably.